Joko Widodo's 'Bebas-Aktif' Foreign Policy Approach: Continuity and Change - Arifin, Saru (Universitas Islam Internasional Indonesia (UIII), 2023)
Unlike his predecessors, Indonesian President Joko 'JokowiJ Widodo was unusually inward looking in his foreign policy approach in his first term (2014-2019). Jokowi often skipped important international diplomacy events, preferring to focus his energy on handling domestic affairs. It resulted in some observers lamented that his choice had degraded lndonesiaJs diplomatic standing internationally. Since the beginning of his second term in 2019, Jokowi has started to be more active in his foreign policy approach. He began to participate in international diplomatic events more than before) and even he has been more active in contributing to international affairs, including in contributing to promote peace. This article argues that foreign policy under the Jokowi presidency is the manifestation of continuity and change.